Simulation and experimental validation of acoustic properties of hollow sphere structures. Issue 5 (May 2014) - Janousch, C.; Winkler1, R.; Wiegmann, A.; Pannert1, W.; Merkel1, M.; Öchsner, A.
<x xml:space="preserve">Abstract</x> Customers nowadays regard the noise and vibration behavior as an essential product property. Cellular character materials, in particular hollow sphere structures, are predestined to absorb sound in a very efficient manner due to their cellular character. Depending on the constituent material, the geometric parameters like the diameter of the spheres, the thickness of the walls and the assembling schema of single spheres, the absorption coefficient can be reduced to very low levels. In contrast to other cellular materials, the frequency and bandwidth can actively be influenced by the variation of the above mentioned parameters. In order to predict the acoustic behavior of a structure, FE or CFD analyses are used as standard tools. In addition, there exist some parameter based models, e.g. the BIOT theory, which characterizes the absorption, transmission and reflection coefficients using a few macroscopic parameters. Within this contribution, the acoustic properties of hollow sphere structures are investigated by a so‐called virtual material laboratory GeoDict (by Math2Market GmbH, originally by the Fraunhofer Institute for Industrial Mathematics). The results for the absorption and reflection coefficients are compared to those gained by classical analysis methods and experiments based on Kundt's tube.